Predicting the Priorities of Multicultural Education in a Philippine Teacher Education Institution: An Exploratory Study - Palces, Krizna Rei M.; Abulencia, Arthur S; Reyes, Wensley M (EDUCARE, 2015)
ABSTRACT: Multicultural education is a contemporary pedagogy, which prepares academic institutions to combat discrimination and oppression. It also aims to maximize learning by creating an environment that is safe and productive. International academic institutions as well as national institutions must take multicultural pedagogy as the best perspective in handling the reality of a pluralistic society. Multicultural education is quite literally the pedagogy of the oppressed. It is a pedagogy that was born out of the struggle of the oppressed sectors in the West such as the African-Americans, women, homosexuals, religious minorities, atheists, indigenous people, the differently-abled, and others. This is the embodiment of the dreams of those who fought for equality and respect. Since many forms of oppression are still existent in various societies, multicultural education continues to receive support from education sectors in many free countries. This paper describes the diversity of learners in a Philippine Teacher Education institution according to classifications of race, ethnicity, class, religion, and gender with the goal of predicting the priorities of multicultural education. The project started with profiling students using a specialized tool beyond demographics. The diagnostic tool identified categories significant for multicultural education. From the demographic, the researchers analyzed various aspects of multicultural education. The researchers identified the levels of diversity and made necessary recommendations needed for multicultural education.KEY WORDS: Multicultural education, race, ethnicity, class, religion, gender, contemporary pedagogy, diversity of learners, Philippine Teacher Education institution, and levels of diversity.Â Â Â Â About the Authors: Krizna Rei M. Palces, Ph.D., Prof. Arthur S. Abulencia and Prof. Wensley M. Reyes are the Lecturers at the Faculty of Behavioral and Social Sciences PNU (Philippine Normal University), Taft Avenue, Manila 1000, the Philippines. For academic interests, the author can be contacted via e-mail at: abulencia.as@pnu.edu.phHow to cite this article? Palces, Krizna Rei M., Arthur S. Abulencia & Wensley M. Reyes. (2015). âPredicting the Priorities of Multicultural Education in a Philippine Teacher Education Institution: An Exploratory Studyâ in EDUCARE: International Journal for Educational Studies, Vol.8(1) August, pp.63-72. Bandung, Indonesia: Minda Masagi Press and UMP Purwokerto, ISSN 1979-7877.Â Chronicle of the article: Accepted (June 4, 2015); Revised (July 6, 2015); and Published (August 25, 2015).